Coronary computed tomography angiography in coronary artery disease. - Sun, Zhonghua; Ng, K. (2011)
AIM: To investigate the research directions of coronary computed tomography (CT) angiography in the diagnosis of coronary artery disease (CAD) based on a systematic review of the literature. METHODS: A search of articles on coronary CT angiography in the diagnosis of CAD was performed during a 6-year-period between 2005 and 2010 from five main radiology journals namely, Radiology, American Journal of Roentgenology, European Radiology, European Journal of Radiology and British Journal of Radiology. Analysis of the references was focused on the research directions of coronary CT angiography with regard to the type of studies in terms of diagnostic value, application of dose-reduction strategies and resultant effective radiation doses with use of these techniques. RESULTS: One hundred and forty two studies were identified which met the selection criteria and were included in the analysis. 64-slice CT (single source and dual-source CT) dominated 78% of the coronary CT angiography studies. Prior to 2007, research was focused on the diagnostic value of coronary CT angiography, but since 2008 more attention has been paid to radiation dose reduction. Radiation dose was reported in 64 studies, representing 45% of total studies published in the five radiology journals. Various dose-saving strategies have been implemented and prospective electrocardiography-triggering and high pitch techniques were found to be the most effective approaches for radiation dose reduction, with the corresponding mean effective dose being 3.5 ± 1.9 mSv and 1.7 ± 0.6 mSv, respectively. CONCLUSION: This review shows that the current research in coronary CT angiography has shifted from the previous focus on diagnostic accuracy in CAD to more emphasis on radiation dose reduction.